Assessing the effect of Lycium barbarum polysaccharides on the formation of heat-induced myofibrillar protein gels - Ziyuan Zhang; Jia Miao; Lin Wang; Jiaqi Tian; Jiayu Xu; Sitong Liu; Qian Liu; Baohua Kong; Juyang Zhao; Fangda Sun (Food Chemistry Advances)
The effect of adding various amounts of Lycium barbarum polysaccharides (LBP) (0–2.5 % (w/w) in increments of 0.5 % (w/w)) on a myofibrillar protein (MP) gel was investigated. The addition of LBP improved the whiteness, water-holding capacity, gel strength, rheological properties, microstructure, viscoelasticity and surface hydrophobicity of the MP gel, as well as increasing the number of intermolecular forces therein. Adding LBP to MP changed the secondary structural characteristics of the latter by transforming β–sheets into β–turns, which expanded the tertiary structure. The number of thiol groups and the tryptophan fluorescence intensity were reduced by interactions between the LBP and the MP gel. Hydrophobic interactions and disulphide bond formation induced by the LBP improved the MP gel strength and induced the gel network structure to become more consistent and tidier.